Sulforaphane Attenuates Endometriosis in Rat Models Through Inhibiting PI3K/Akt Signaling Pathway. Issue 2 (10th June 2019) - Zhou, Aixiu; Hong, Yiting; Lv, Yuchun
Sulforaphane exerts anti-inflammatory activity in inflammatory diseases. The endometriosis (EM) is accompanied by chronic inflammation. The present study aims to explore the therapeutic effects of sulforaphane on EM and its underlying mechanism. An EM rat model was established by transplantation of autologous fragments. The rats were intragastrically administered sulforaphane (5 mg/kg, 15 mg/kg, and 30 mg/kg) for 3 weeks. The volumes of endometriotic foci and adhesion score were calculated at the end of the experiment. Levels of interleukin (IL)-6, IL-10, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, and vascular endothelial growth factor (VEGF) were determined by enzyme-linked immunosorbent assay (ELISA). Expressions of VEGF, B-cell lymphoma/leukemia 2 (Bcl-2), Bax, cleaved caspase-3, PI3K, and Akt in endometrial tissue were determined by Western blotting. Relative expressions of PI3K and Akt were determined by quantitative polymerase chain reaction. Posttreatment of sulforaphane dose-dependently decreased the volumes of endometriotic foci and adhesion score in EM model. Additionally, posttreatment of sulforaphane inhibited levels of IL-6, IL-10, TNF-α, IFN-γ, and VEGF in peritoneal fluid and plasma. Posttreatment of sulforaphane regulated the expressions of VEGF, bcl-2, Bax, and cleaved Caspase-3 in EM model. The underlying mechanism revealed that sulforaphane attenuated EM in the rat model by inhibition of PI3K/Akt signaling pathway.